Association of Maternal Factors with Low Birth Weight Newborns - Hamayun Anwar; Anila Farhat; Ajaz Ahmed; Bushra Bashir; Khalid Khan; Irfan Khan (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To determine the association of maternal factors with low birth weight (LBW) newborns at King Abdullah Teaching Hospital, Mansehra. METHODOLOGY: This descriptive cross-sectional study was done at the Department of Pediatrics and labor room of King Abdullah Teaching Hospital, Mansehra, Pakistan, from June to November 2021. A total of 171 women aged 18-30 who had a singleton pregnancy ?37 completed weeks of gestation were enrolled and evaluated for the presence of risk factors associated with the incidence of LBW in infants. The outcome regarding the frequency of low birth weight and its associations with Maternal factors were recorded. RESULTS: In a total of 171 women, 77(45.0%) had short stature, while 57(33.3%) weighed 50 kg or less. The frequency of anemia was noted in 56 (32.7%). Out of 171 women who gave a singleton live birth, 63(36.8%) newborns were LBW. A significantly less proportion of mothers had maternal age between 18-25 who delivered LBW babies (74.6% vs. 44.4%, p=0.0001). Short stature among mothers was significantly associated with LBW (58.7% vs. 37.0%, p=0.0060). Maternal weight less than or equal to 50 kg was also linked with LBW (42.9% vs. 27.8%, p=0.0436). Anemia is significantly associated with LBW (49.2% vs 23.1%, p=0.0005). CONCLUSION: The frequency of LBW was noted to be high. Maternal age between 18-25 years, short stature, low maternal weight (>50 kg), and anemia during pregnancy can significantly raise the risk of LBW.